Entrepreneurship, Creativity, and Self-directed Learning: Learning Strategies for Children - Setiawan, Iyan; Nurisman, Husain; Megayanti, Windi; Tri Wibowo, Wahyu (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The purpose of this research is to determine the relationship between creativity and learning toward entrepreneurship. It emphasizes the importance of integrating these elements into children education to promote entrepreneurial values and future success. Method: This research employed a mixed-method approach, combining quantitative (questionnaires using SPSS 26) and qualitative (observations, interviews, and documentation) techniques. The study involved 31 fifth and sixth-grade elementary school students in Bogor Regency. Normality and homogeneity tests were conducted to ensure data validity before further statistical analysis. The goal was to determine the relationship between creativity and learning toward entrepreneurship Results: The results indicated a strong relationship between creativity, self-directed learning, and entrepreneurship in elementary school children. The statistical analysis showed that creativity and self-directed learning have a significant influence (97.2%) on entrepreneurship. Qualitative data supported these findings, highlighting the importance of fostering these skills. Novelty: This research uniquely explores the interplay between creativity, self-directed learning, and entrepreneurship in elementary education. It provides empirical evidence of their interconnectedness and offers insights into fostering these skills in young children. The study also recommends further exploration of entrepreneurship education in children contexts.